Transforming ‘Chalk and Talk’ Teaching and Learning for an Undergraduate Mathematics Course during COVID-19 Outbreak - Sarah Flora, Samson Juan; Hamimah, Ujir; Tiong, Wei King; Nuha Loling, Othman; Shapiee, Abd Rahman; Phang, Piau (UMK Press, 2021)
‘Chalk and talk’ is commonly used as one of the methods to teach mathematics courses due to its simple strategy of demonstrating and solving mathematics problem on the whiteboard in front of the whole class. In UNIMAS, the Faculty of Computer Science and Information Technology lecturers have been using this method as a medium to teach first year undergraduate students undertaking TMF1874 Mathematics for Computing. However, when the COVID-19 pandemic situation escalated in March 2020, the method had to be changed to fit student’s needs for online learning. University students were sent back home after Malaysian government announced the movement control order (MCO) in a bid to fight the virus (Hassan, 2020). At that time, there were 300 undergraduate students taking the course and they had already gone through half of the syllabus through physical lecture and tutorial sessions. The common strategy was disrupted, and an ad-hoc plan was required to have a fully online teaching and learning for the remaining weeks of the semester. There were three challenges that need to be considered: How to ensure that all students can access the materials online? How to create online assessments for many students? What are the ways to communicate with the students to check on their progress?